PROFIL PERSONAL HEALTH BEHAVIOR KARYAWAN FMIPA UNIVERSITAS NEGERI YOGYAKARTA - Mariyam, Siti; Pertiwi, Kartika Ratna (FKM - UNEJ, 2014)
Human behavior comes out as the result of a continuous interaction between human and his environment. This research aims to capture personal health behavior (PHB) status of employees from FMIPA UNY, and to analyse factors involved in determining the PHB profile. The result is beneficial to be used as a database to design a university policy regarding to the alteration of health behavior to improve the employeesâ health status. The study was designed as an analytical survey, cross sectional model, with point time approach. The respondents were employees from FMIPA UNY, taken by incidental sampling technique. PHB score was obtained from Personal Health Inventory (PHI) questionnaire adapted from Getchell (1991. Data were analysed descriptively and the relationship between variables was cross-tabulated. The results showed that there were no differences of PHB score between male and female and between age range. According to their PHB score, almost employees (97,96%) were in moderate risk. Factors involved in PHB profile were predominanty individual health history and social economic status. It is suggested that the employees should be more aware on their health behavior to reduce their risk against health diseases and disorders. Keywords: health behavior, employee, characteristics, individual history